157 AN UNUSUAL PRIMARY PRESENTATION OF NEPHROTIC SYNDROME AS RENAL VEIN THROMBOSIS: A HUNT FOR THE HIDDEN CAUSE!. Issue 1 (1st January 2007) - Rehmani, R.; Contractor, D.; Niranjan, S.; Godkar, D.
Abstract : Background: Bilateral renal vein thrombosis (RVT) could be due to many different etiologies with varying primary presentations. RVT is often difficult to diagnose early on in the disease process as the patients are often asymptomatic and renal insufficiency is mild or absent. In adults, primary RVT is most commonly due to nephrotic syndrome typically of membranous type. In fact, 40% of RVT in adults is attributed to nephrotic syndrome. Case Report: We present a case of a 40-year-old man who presented with gradually progressing left-sided pleuritic chest pain, shortness of breath, and nonproductive dry cough for 2 months that worsened over the past 2 weeks. Initial chest radiography was reported as normal. A chest CT scan with contrast was obtained that revealed massive bilateral pulmonary artery embolism with lung tissue infarction. Upon further biochemical tests and appropriate radiologic investigations, it was revealed that the source of his pulmonary embolism was, in fact, thrombosis of both his renal veins. This was correlated with the laboratory tests that demonstrated massive proteinuria (11 g/d) and hypoalbuminemia (1.2 g/dL) and hypercholesterolemia, which uncovered the diagnosis of nephrotic syndrome. Discussion: Nephrotic syndrome can complicate any disease that disturbs the negative electrostatic charge of GBM and the podocytes and their slit diaphragms. Nephrotic syndrome is a clinical complex characterized by several renal and extrarenal manifestations, such as proteinuria (3.5 g/1.73 m 2 /24 h), hypoalbuminemia, edema, hyperlipidemia, lipiduria, hypercoaguability, peritonitis, congestive heart failure, and generalized prothrombotic changes resulting in pulmonary embolism, RVT, and stroke. Spontaneous peripheral and arterial thrombosis, RVT, and pulmonary embolism can develop due to hypercoagulability during nephrotic syndrome. The cause of hypercoagulability is multifactorial, including altered levels of proteins C and S, urinary loss of antithrombin III, hyperfibrinogemia due to increased hepatic synthesis, impaired fibrinolysis, and increased platelet aggregability. Platelet activation and aggregation is further stimulated by high plasma concentrations of cholesterol, fibrinogen, and VWF. Learning Point: The purpose of this abstract is to present an unusual cause of PE in a young patient. An astute clinical suspicion led to an early diagnosis of the RVT in this patient and hence initiation of early treatment and full recovery within few months.